The Effect of Multiwalled Carbon Nanotubes on Hepatotoxicity of Cd2+ in Accumulated Cadmium-Metallothione in Mice. (2nd September 2014) - Wei, Qi; Juanjuan, Bi; Longlong, Tian; Zhan, Li; Peng, Liu; Wangsuo, Wu
Abstract : The effects of oxidized multiwalled carbon nanotubes (oMWCNTs) on the behavior and hepatotoxicity of Cd 2+ in accumulated cadmium-metallothionein mice were investigated. The results indicated that, after exposure of oMWCNTs to normal mice, oMWCNTs could not induce the liver to produce metallothionein (MT). When exposing Cd-MT mouse to different doses of oMWCNTs oMWCNTs could cause Cd 2+ release from the accumulated Cd-MT; subsequently, one part of the free Cd 2+ was eliminated with blood circulation; the other part adsorbed by oMWCNTs would remain in the tissues together with oMWCNTs. The results of the activities changes of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TB), and blood urea nitrogen (BUN) in plasma showed that the hepatotoxicity of coexposure was lower than that of single exposure, and the hepatotoxicity and accumulation of oMWCNTs in livers depended strongly on the exposure dosage of oMWCNTs. The histology of liver and kidney tissue also confirmed the previous results. Therefore, the author inferred that MT could be connected with oMWCNTs to reduce their hepatotoxicity, but the detailed mechanism needs to be further studied.